Self-Evaluation of Nurses and Midwives Practices Using SBAR (Situation, Background, Assessment, Recommendation) Communication Tool on Maternal Health Documentation - baqer, Sundus; Ali, Rabea; Bahaaldeen, Ezedeen (Iraqi National Journal of Nursing Specialties, 2018)
Abstract:Objective: To self-evaluate the effect of SBAR (Situation, Background, Assessment, and Recommendation) educational program on nurse and midwives practices in maternal health report documentation accuracy.Methods: A quasi- experimental design was carried with the application of pre- post test for nurses and midwives’ knowledge and practices regarding SBAR communication tool. The study was held in Al-Elwia maternity teaching hospital, Al –Karckh maternity hospital and Al-Yarmouk teaching Hospital. purposive sample as it was convenient with inclusion criteria consisted of (84) nurse and midwives. The questionnaire comprised of demographic data, nurses- midwives practices of SBAR using (5) level Likert scale for assessment, with Cut –off point (3). Content validity was determined through (21) expert. Pilot study was conducted on (10) nurses and midwives at Al- Elwia maternity teaching hospital during 15th to 22nd ,may, 2017. Reliability of the questionnaire (pre (0.89), post (0.89), evaluation (0.936) Descriptive and Inferential statistical data analysis were used.Results: The result shows that there is significant statistical differences in all domain, so we reject the nil ( ) hypotheses and accepted the alternative one ( ). Because the calculate value greater than table value for each degree of freedom (3,4) that corresponding the table value (7.816 ,9.488) respectively. The means are not equal for all in chi- square distribution and in the corresponding degree of freedom. No significant differences between evaluation variable (practice) in SBAR program with the socio-demographic characteristics, except for work place shows significant differences at (P-value : 0.000). The results also presents that participants were extremely confident in applying scenario for Placenta praevia, Abortion, Teenage pregnancy, Postdate pregnancy, Preeclampsia, and last Premature rupture membranes. Recommendations: A coordination with Ministry of health in Iraq- to activate SBAR forma to be used in nursing curriculum. Encouraging nurse –midwives to attend workshop, conference training programs and review nursing care related to SBAR forms.